The Importance of Translation Skills in the Study of Scientific and Literary Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the emergence and development of translation studies, problems in the field of translation, and how important the field of translation is in scientific and artistic works. Examples of the researches of several scientists in the field of translation are also given.